O pibid na construção dos saberes e práticas para o ensino de história: um estudo a partir de narrativas (auto)biográficas - Cordeiro, Fátima Nailena da Fonsêca (2019)
This master's thesis focuses on the (self) biographical narratives of teachers who participated, during undergraduate, from the Institutional Scholarship Program for the Initiation to Teaching- PIBID of the licentiate (degree) course in History. The general objective is to analyze the meanings attributed by the teachers to the PIBID and to deduce with them the possible contributions to the construction of their knowledge and practices in the teaching of history in Basic Education. The specific objectives seek: 1) Understand how the graduates of PIBID, understand and mean their experiences in the program; 2) Point out and reflect the implications of PIBID in the construction of knowledge and practices for the teaching of history; 3) Apprehend which feelings were mobilized from (self) biographical narratives. Research is part of a qualitative approach and is based on the principles of (biographical) research and theories for the teaching of History. Five teachers participated in this research, who lived their experiences in the PIBID between the years 2012 to 2016. The corpus used for analysis is constituted by 05 (five) narrative interviews, as well as records in the field journal of the researcher. The sources were produced in the months of August to September 2018. The analysis based on the conceptions of Jovchelovitch and Bauer (2002), led us to the following findings: comprehension, understanding and perceptions of PIBID by graduates; the PIBID and the teaching of history, its collaborations to the construction of learning; the PIBID as a course of formative learning, and the memories of pedagogical experiences provoked by the act of narrating. We conclude that initiatives such as the PIBID collaborate in the educational development of the country, in this sense, we show, with the narratives of the graduates of the PIBID, that investments in public policies of this nature can attenuate some of the problems experienced in the scenario of Brazilian education